(untitled) (Biological Sciences - PJSIR, 2000)
Solid state copolymerization of acrylamide (r.) and cinnamic acid (r2) was accomplished under UV radiation at a tem- perature 68°C below the melting point of monomers. It is noted that yield of the product does ot repeat but trend remains the same. The monomer reactivity ratios were determined to be rl=I.6 and r2= O. Molecular weights of the product samples range between 11205 -72770. All copolymer samples are off-white solid substances that become light yellow at 140°C.